PRINCIPLES OF RESEARCH AND THE SPECIFIC FEATURES OF ENSURING FINANCIAL SECURITY OF THE BUSINESS SECTOR IN UKRAINE - LYNDA, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of this study is to substantiate the theoretical and methodological foundations of research and to identify the specific features of financial security within the small business sector in the region. Scientific approaches to the essential interpretation of the concept of the state’s financial security have been generalized. Key characteristics of the theoretical and methodological foundations of enterprise financial security are presented. The semantic particularities of the concept of economic security at the level of industry and sector of the national economy are revealed. On this basis, the theoretical and methodological foundations for studying economic and financial security at various levels of economic development management have been formulated. It has been established that the financial security of the small business sector is characterized by: (1) the state of protection of its entities from internal and external financial and economic challenges and threats, their financial provision, financial and economic efficiency, strength and balance of financial condition, stability and solvency, as well as capitalization trends at the micro level and within the financial system as a whole; (2) the degree of realization of the financial and economic interests of stakeholders in this sector; (3) the capacity of the state to guarantee financial security and stability of the sector, especially at the regional level. The internal structure of the financial security of the regional small business sector has been determined. The scientific novelty of the research lies in the further development of the theoretical and methodological foundations of financial security research at the sectoral level by defining its internal structure specifically for the small business sector of the region. This structure consists of components: (1) market and legal capacity; (2) sustainability, efficiency, and protection (against risks and threats, as well as the financial and economic efficiency of management and investment); (3) development (the ability to maintain a sustainable trajectory of improvement in key financial and economic indicators both for individual entities and the sector as a whole). The structural components of the financial security of the small business sector in the region include resource, financial and economic, investment, monetary, insurance, and debt components.